Severe Enamel Defects in Wild Japanese Macaques - Ian Towle; Carolina Loch; Marina Martínez de Pinillos; Mario Modesto-Mata; Leslea J. Hlusko (International Journal of Zoology)
Plane-form enamel hypoplasia (PFEH) is a severe dental defect in which large areas of the crown are devoid of enamel. This condition is rare in humans and even rarer in wild primates. The etiology of PFEH has been linked to exposure to severe disease, malnutrition, and environmental toxins and associated with systemic conditions. In this study, we examined the prevalence of enamel hypoplasia in several populations of wild Japanese macaques (Macaca fuscata) with the aim of providing context for severe defects observed in macaques from Yakushima Island. We found that 10 of 21 individuals (48%) from Yakushima Island displayed uniform and significant PFEH; all 10 specimens were from two adjacent locations in the south of the island. In contrast, macaques from other islands and from mainland Japan have a low prevalence of the more common types of enamel hypoplasia and none exhibit PFEH. In Yakushima macaques, every tooth type was affected to varying degrees except for first molars and primary teeth, and the mineral content of the remaining enamel in teeth with PFEH was normal (i.e., no hypo- or hypermineralization). The aetiology of PFEH might be linked to extreme weather events or high rates of environmental fluoride-causing enamel breakdown. However, given that the affected individuals underwent dental development during a period of substantial human-related habitat change, an anthropogenic-related etiology seems most likely. Further research on living primate populations is needed to better understand the causes of PFEH in wild primates.